2020
DOI: 10.1101/2020.02.04.934570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Impacts on Host Transcription by ROP and GRA Effectors from the Intracellular ParasiteToxoplasma gondii

Abstract: words 16Importance: 36 words ABSTRACT 30The intracellular parasite Toxoplasma gondii employs a vast array of effector 31 proteins from the rhoptry and dense granule organelles to modulate host cell biology; 32 these effectors are known as ROPs and GRAs, respectively. To examine the individual 33 impacts of ROPs and GRAs on host gene expression, we developed a robust, novel 34 protocol to enrich for ultra-pure populations of a naturally occurring and reproducible 35 population of host cells called uninfected-in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Prior to reverse transcription (RT), the RNA for one of the C3 subclone samples was divided into two aliquots to serve as a technical replicate control (C3ci and C3cii). All samples were prepared for RNA sequencing using the Nextera XT Library preparation kit and the libraries were run on the NextSeq500 platform following a protocol adapted from Rastogi et at (37). Reads were aligned to concatenated human and Toxoplasma ME49 genomes using the method described in Xue et at (26).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to reverse transcription (RT), the RNA for one of the C3 subclone samples was divided into two aliquots to serve as a technical replicate control (C3ci and C3cii). All samples were prepared for RNA sequencing using the Nextera XT Library preparation kit and the libraries were run on the NextSeq500 platform following a protocol adapted from Rastogi et at (37). Reads were aligned to concatenated human and Toxoplasma ME49 genomes using the method described in Xue et at (26).…”
Section: Resultsmentioning
confidence: 99%
“…Akin to the immune cell transcripts, several models could account for the parasite transcripts being in only the TIN transcriptomes. As recent papers have shown that uninfected-injected host cells have different transcriptional profiles than fully invaded cells and that these differences are driven by the parasite effectors that are released before full invasion (rhoptry proteins) versus after invasion (specific dense granule proteins) ( 39 , 62 ), follow-up studies using single-cell RNA-seq should be able to identify if an individual TIN arose from aborted invasion or from invasion followed by clearance of the intracellular parasite. Such studies may even be able to distinguish between previously infected neurons and actively infected neurons.…”
Section: Discussionmentioning
confidence: 99%
“…To predict the cell cycle phase of individual single cells, we curated a list of cell cycle related genes (S, and G2/M)(82). We then used the “score_genes_cell_cycle” function in Scanpy package to annotate the cell cycle phase of each cell.…”
Section: Methodsmentioning
confidence: 99%